Parenting, between radicalism and ideology - Alfano, Linda; Lorettu, Liliana; Monteleone, Roberta; Ciliberti , Rosagemma (Medicina Historica, 2022)
As has been the case for several years in many countries, in Italy, new continuing forms of family composition, as well as increasingly complex forms of parenting, are sharply taking root.These innovations are often accompanied by criticisms and (pre)conceptions that (in)form our traditional and consolidated way of thinking about the family.Issues related to the right of the child to pursue his or her best interests and the possible functioning of the family constellations with non-genetic links are feeding important ethical questions.The careful analysis of scientific literature suggests freeing oneself from ideological approaches to base assessments and choices on the data available within psychological studies on the phenomenon.The commitment of professionals working with children is to welcome the complexity of today’s families without stigmatizing, pathologizing, or ideologizing.